Error Analysis and Parameter Design of Spatial Path Generation Algorithm “SmarTrack” by the Complementary Use of Nominal Path Data and Sensory Path Data - KAKIZAKI, Takao; NONAKA, Kiyoshi (Nihon Kikai Gakkai rombunshuu. C hen, 2004)
This paper describes error analysis and parameter design of robot seam tracker algorithm. The algorithm discussed in this paper is called SmarTrack Algorithm which has been proposed by the authors and can realize a high reliability robot seam tracker system that can operate even under poor sensing environments. First, the error constituents of the path restored by this Algorithm are identified analytically. Then, the relationships between algorithm parameters and the path restoration characteristics of this Algorithm are evaluated by simulation when sensing interval and standard deviation of sensing error are given. Based on the results, algorithm parameters design criterion for a high reliability robot seam tracker system is given.